2009
DOI: 10.29333/ejgm/82671
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms in Turkish adolescents

Abstract: Aim: To determine the prevalence of depressive symptoms in adolescents and explore the association of socio-demographic factors with depression. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
3
15
0
4
Order By: Relevance
“…Since the CDRS-R, unlike the MINI-kid, was not designed to identify other mental disorders such as bipolar and anxiety disorders, we were unable to report on other potentially co-morbid mental health conditions. Studies in both HIV-positive and uninfected adolescents and adults have demonstrated that females show higher rates of depression compared to males [22,23,45,46]. In our study, the difference in prevalence of depression between genders appeared to be considerable, and we found a statistically significant difference in mean CDRS-R scores between genders.…”
Section: Discussionsupporting
confidence: 50%
“…Since the CDRS-R, unlike the MINI-kid, was not designed to identify other mental disorders such as bipolar and anxiety disorders, we were unable to report on other potentially co-morbid mental health conditions. Studies in both HIV-positive and uninfected adolescents and adults have demonstrated that females show higher rates of depression compared to males [22,23,45,46]. In our study, the difference in prevalence of depression between genders appeared to be considerable, and we found a statistically significant difference in mean CDRS-R scores between genders.…”
Section: Discussionsupporting
confidence: 50%
“…In our study group, students in 2 nd pre-university college had highest rates of depression (64.5%) followed by students in 10 th class (59.8%). Our finding of increasing rates of depression with students scoring lesser marks was similar to that found in a study in Turkey by Said Bodur et al 7 . Students in residential schools were significantly more depressed compared to non-residential schools.…”
Section: Discussionsupporting
confidence: 80%
“…While there are other studies that found significant relationship between age and depression [20,21]. This finding should be interpreted with caution, as this was because the participants were in one secondary grade and they were close in their ages.…”
Section: Discussionmentioning
confidence: 47%